Dynamic SIMS, spectroscopic ellipsometry and x-ray diffractometry analysis of SiGe HBTs with Ge grading. (14th December 2018) - Bärwolf, F; Fursenko, O; Zaumseil, P; Yamamoto, Y
Abstract: In this paper, SiGe heterojunction bipolar transistors (HBTs) with Ge concentrations up to 40 atomic percent (at%) and different slopes of Ge gradients are characterized by comparing dynamic secondary ion mass spectrometry (D-SIMS) and multi-angle spectroscopic ellipsometry (SE). X-ray diffractometry (XRD) was used as reference. D-SIMS results show that sputter rate and Ge content calibration have major impact on depth profile measurements of HBTs with graded SiGe. Strained and relaxed SiGe show differences in Ge content calibration and no difference in sputter rate calibration. Jiang's protocol was used for Ge content calibration and proven to be valid up to ∼50 at% Ge. SE with a combination of 3 angles of incidence (AOIs) (59, 65, 71°) in comparison with the single AOI (71°) realized in industrial setup for semiconductor manufacturing environment was analyzed to find a more stable solution for revealing the thickness of plateau and gradient parts of SiGe base. SE with 71° AOI and rotating compensator is the best choice for in-line HBT with Ge grading characterization. The determination of gradient shape continues to be a challenging task for SE, due to high parameter correlations and the need to use some fixed parameters within the fitting procedure. D-SIMS remains the favorite for graded profile determination. Results of D-SIMS and SE with fixed parameters are in good agreement with XRD for HBTs with Ge grading.